(In) sustainability of natural resources in the scope of international comercial negotiations: the case of water (Polis (Santiago), 2018)
We start out stating that a double speech is being developed from de point of view of the sustainability of natural resources in general, on diversity and particularly on water. Concepts of intergenerational equity, conservation of the resources, sustainable use, participation, and social control are being used by social organizations and NGO’s, as well as in business forums, public institutions, and IFI’s, Financial Multilateral Institutions, with a very different meaning. The topic of water rights as investor’s rights, and intellectual property rights applied to living matter, and ancestral knowledge are examples of an unsustainable treatment of natural resources, because they are granting privilege to the commercial over the environmental meaning.
Keywords: equity; water; natural resources; international commerce